Relevansi Nilai PSAK 73: Studi Pasar Modal Indonesia - Jonatan, Arif; Koeswayo, Poppy Sofia; Puspitasari, Evita (Jurnal Riset Akuntansi dan Keuangan, 2021)
Accounting standard and treatment for leasing is one that draws a lot of debate. Accounting treatment for leasing in PSAK 30 causes off-balance sheet transactions, where assets and liabilities of a leasing transaction are not recorded on financial statements. PSAK 73 introduces Right-of-Use model that could reflect leasing transactions on financial statements. This introduction is expected to increase the value relevance of financial statement for its users. Does PSAK 73 truly increase value relevance of financial statements? The authors answered the question by performing empirical research of value relevance in Indonesian Stock Exchange, especially constituents of Kompas 100 index, using Ohlson (1995) model. Authors found that contrary to expectation, PSAK 73 does not necessarily increase value relevance of financial statements for its users Although, it’s indicated that its relevance depend on the intensity of lease transactions to the company’s business. Authors discussed findings, along with recommendations for future research. Standar dan perlakuan akuntansi sewa adalah standar yang menuai banyak perdebatan. Perlakuan akuntansi sewa dalam PSAK 30 membuat adanya transaksi off-balance sheet dimana aset dan liabilitas dari suatu transaksi tidak tercatat dalam laporan keuangan. PSAK 73 memperkenalkan model Right-of-Use yang dapat merefleksikan transaksi sewa dalam laporan keuangan. Hal ini diharapkan akan meningkatkan relevansi laporan keuangan bagi penggunanya. Apakah PSAK 73 benar meningkatkan relevansi laporan keuangan? Penulis menjawab hal tersebut dengan melakukan penelitian empiris relevansi nilai di pasar modal Indonesia, terutama perusahaan konstituen Kompas 100, menggunakan model Ohlson (1995). Penulis menemukan bahwa bertentangan dengan ekspektasi, PSAK 73 tidak serta merta meningkatkan relevansi nilai laporan keuangan bagi penggunanya. Meski begitu, terindikasikan bahwa relevansi nilai PSAK 73 bergantung pada intensitas transaksi sewa bagi bisnis perusahaan. Penulis mendiskusikan temuannya, beserta dengan rekomendasi untuk penelitian selanjutnya